BIOSINTESIS NANOPARTIKEL PERAK (AgNPs) DENGAN EKSTRAK DAUN KIRINYUH (Chromolaena odorata) TERIMPREGNASI ZEOLIT DALAM MENGHAMBAT BAKTERI PENYEBAB JERAWAT - Mariani, Hulya; Mahdi, Nisful; Umam, Khotibul (LP4MK STKIP PGRI Lubuklinggau, 2023)
Acne is a chronic inflammation of the human skin. One of them is caused by the activity of the oil glands that produce excess sebum to cover the pores and is exacerbated by the presence of bacterial infections, namely Staphylococcus epidermidis and Propionibacterium acnes. Silver nanoparticles (AgNPs) are one of the most widely synthesized uses of nanotechnology because they are toxic to bacterial cells so that they can be used as antibacterial agents. This study aimed for the biosynthesis effectivity against acnes bacteria. The method was using experimental research with analyze the data through ANOVA. The results showed that zeolite-impregnated AgNPs had the potential as antibacterial agents against acne-causing bacteria that had strong inhibition as evidenced by the diameter of the inhibition zone formed on Staphylococcus epidermidis and Propionibacterium acnes in the range of 11-20 mm at any given concentration used. Based on the average diameter of the inhibition zone formed, it can be seen that the largest inhibitory zone occurred at 15 mm and 20 mm AgNO3, with 18 mm in Staphylococcus epidermidis and 14.6 mm in Propionibacterium acnes bacteria respectively. This study was the first initially test the AgNPs effect to the acne’s bacteria and its further potential for anti-acnes.